Potential impacts of Acu-TENS in the treatment of adolescents with moderate to severe bronchial asthma: A randomized clinical study - Ragab K. Elnaggar; Samah A. Moawd; Shaimaa E. Ali; Abeer M. Yousef; Alshimaa R. Azab (Elsevier, 2021)
Objective: The purpose of this study was to evaluate the efficacy of transcutaneous electrical nerve stimulation over the acupuncture points (Acu-TENS) on total serum immunoglobulin E (IgEtotal), pulmonary function, and quality of life in adolescents with asthma. Methods: In a double-blind randomized clinical trial, 32 adolescents (age; 12-16 years) with asthma participated and were assigned randomly to receive either the breathing retraining program (control group) or the breathing retraining program plus Acu-TENS application (Acu-TENS group). Acu-TENS was applied for 40 min' day-after-day session for two successive months, with no side-effects reported. Serum IgEtotal, pulmonary function [forced vital capacity (FVC), forced expiratory volume at one second (FEV1), and FEV1/FVC], and quality of life were evaluated pre- and post-treatment. Results: Serum IgEtotal (P = 0.028, ηp2 = 0.15), Pulmonary function [FVC (P = 0.043, ηp2 = 0.13), FEV1 (P = .046, ηp2 = 0.12)], and quality of life (P < .001, ηp2 = 0.17) increased significantly in the Acu-TENS group when compared to the control group. Conclusion: This study demonstrates that the Acu-TENS is an impending asthma treatment that may be used to reinforce the immune system response, ameliorate lung function, and increase the quality of life in adolescents with asthma.